Future Cities: New Generation's Visions of Sustainability Concepts and Models. Issue 1 (30th April 2019) - Likitswat, Fa
The creation of sustainable cities for unpredicted and uncertain futures requires and involves a broad range of disciplines. Our living conditions within the cityscape are a consequence of the actions of the past generation, while cities shape the next generation's way of life. Some of the key challenges in shaping our future cities are not only our behavioural changes but also the redesign and restructuring of the built environment to make it more liveable and give it a sustainable urban form. On the basis of the empirical evidences obtained from the Life and Sustainability classes at Thammasat University, in this study, I critically evaluated the sustainability concepts and models of sustainable future cities from the young generation's perspective. Zero energy, quality of life, green infrastructure, city resilience, and combined approach were the five main concepts explored. The analysis shows the students' perceptions and learning outcomes of sustainable concepts and models. By using the built environment module as an example, I collected data 1, 735 undergraduate students enrolled in the fall semester of 2016 and closely re-examined 35 group projects. The results revealed that most of the students were familiar with the two concepts of quality of life and green infrastructure. However, there found it difficult to develop their vision of future cities on the basis of the concept of quality of life. The relationship between the new generation's perceptions of sustainability concepts and the conceptualised prototypes or models of future cities from their understanding was analysed from a socio-economic perspective. Finally, in this paper, I suggest that these two concepts, namely green infrastructure and quality of life, be used as the core concepts along with the other sub-concepts to develop the discussion towards the design and development of future cities.